Crystal structure of the catalytic domain of a GH16 β-agarase from a deep-sea bacterium, Microbulbifer thermotolerans JAMB-A94. Issue 4 (3rd April 2015) - Takagi, Emiko; Hatada, Yuji; Akita, Masatake; Ohta, Yukari; Yokoi, Gaku; Miyazaki, Takatsugu; Nishikawa, Atsushi; Tonozuka, Takashi
Abstract: A deep-sea bacterium, Microbulbifer thermotolerans JAMB-A94, has a β-agarase ( Mt AgaA) belonging to the glycoside hydrolase family (GH) 16. The optimal temperature of this bacterium for growth is 43–49 °C, and Mt AgaA is stable at 60 °C, which is one of the most thermostable enzymes among GH16 β-agarases. Here, we determined the catalytic domain structure of Mt AgaA. Mt AgaA consists of a β-jelly roll fold, as observed in other GH16 enzymes. The structure of Mt AgaA was most similar to two β-agarases from Zobellia galactanivorans, Zg AgaA, and Zg AgaB. Although the catalytic cleft structure of Mt AgaA was similar to Zg AgaA and Zg AgaB, residues at subsite −4 of Mt AgaA were not conserved between them. Also, an α-helix, designated as α4′, was uniquely located near the catalytic cleft of Mt AgaA. A comparison of the structures of the three enzymes suggested that multiple factors, including increased numbers of arginine and proline residues, could contribute to the thermostability of Mt AgaA. Abstract: : Structure of Microbulbifer thermotolerans β-agarase ( Mt AgaA), and the substrate-binding sites of Mt AgaA (red) and Zobellia galactanivorans β-agarases, Zg AgaA (green) and Zg AgaB (blue).